Evaluación de un proceso de fitorremediación en suelo proveniente del municipio de Guamal, Meta, contaminado por desechos de fluidos de perforación base agua con altos contenidos de metales pesados. (2022)
The present work is developed from an experimental scale carried out in laboratories, with a focus on the area of soil bioremediation, by means of the Brassica Juncea plant, subjecting the soil coming from Guamal, Meta due to the proximity to the Castilla field being contaminated with a drilling fluid that has heavy metal content, focusing on the metals Cadmium (Cd) and Chromium (Cr) that come from the friction generated by the drill string, quantifying them by means of the cold HF digestion method - atomic absorption quantification, to determine the concentration of Cadmium (Cd) and Chromium (Cr) present in the soil before and after the phytoremediation process.